Edukasi Kesehatan dan Pemeriksaan Kesehatan Gratis dalam Upaya Meningkatkan Derajat Kesehatan Masyarakat Desa Banyumulek Lombok Barat - Atfal, Bustanul; Hijriani, Baiq Isti; Hadiatun, Nurul; Ismatullah, Nurul Khatimah; Fardani, Roushandy Asri (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Non-communicable degenerative diseases are chronic conditions that do not spread from one individual to another. The incidence of non-communicable diseases continues to increase, along with changes in people's lifestyles that tend to be unhealthy. In NTB Province, some of the main risk factors for non-communicable diseases include hypertension, obesity, and diabetes. The low level of public knowledge and awareness of the dangers of these diseases makes early detection services at health facilities less than optimal. In addition, many people are reluctant to have themselves examined if they have not felt any symptoms of illness. Therefore, risk factor management approaches and community-based prevention efforts are important steps to reduce the risk and mortality of non-communicable diseases. This activity aims to increase public awareness about the importance of routine health checks as part of early detection of non-communicable diseases to improve public health status. The activity was carried out through two methods, namely interactive counseling and direct health checks on participants. In general, the examination results showed a fairly good health condition of the participants with most of the results being within normal limits. However, there were seven participants with blood sugar levels exceeding 300 mg/dL. Activities like this are considered effective in raising public awareness of the importance of routine health checks as a preventive measure for non-communicable diseases.